Self-Efficacy dalam Olahraga: Kajian Bibliometrik: Identifikasi Kontributor Utama dan Arah Perkembangan Penelitian Self-Efficacy dalam Olahraga melalui Pendekatan Bibliometrik - Wulan, Nabella Ayu; Bintari, Dini Rahma (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2025)
Objectives of this study are to map the historical developments, major trends, academic collaborations, and dominant themes in self-efficacy research in the field of sports and physical activity from 1982 to 2025. This study also identifies key contributors and future research directions using a bibliometric approach. Methods Data were collected from the Scopus and Web of Science databases using relevant keywords such as "self-efficacy" and "sport" or "physical activity. The analysis was conducted with the help of VOSviewer software to visualize collaboration networks, keyword co-occurrence, and thematic dynamics. Bibliometric indicators such as publication count, citations, h-index, and annual trends were used to describe the research landscape. The analysis shows that self- efficacy is a central concept strongly associated with motivation, athletic performance, rehabilitation, and mental health. More than 3,000 publications were identified during the analysis period, with a significant increase occurring since the early 2000s. The United States was recorded as the most productive country, with the University of Illinois as the top contributing institution, while Edward McAuley and Albert Bandura were identified as the most cited authors. The findings provide a foundation for developing evidence-based interventions and encourage multidisciplinary collaboration and more inclusive, sustainable sports policies.